Effect of Thickness and Bonding Technique on Fatigue and Fracture Resistance of Feldspathic Ultra-Thin Laminate Veneers - Al-Ali, Amna Mohamed Ahmed Hassan; Khalifa, Nadia; Hadj-Hamou, Amir; Sheela, Soumya; El-Damanhoury, Hatem M. (European Journal of Dentistry, 2022)
Objectives To evaluate the fatigue and fracture resistance of ultra-thin laminate veneers (UTLV) with two different thicknesses and two different bonding protocols.Materials and Methods A total of 64 flat enamel surfaces were assigned to either 0.2 or 0.4 mm UTLV. The UTLV were further subdivided and assigned to one of two bonding techniques: adhesive resin cement(RC( or preheated restorative resin composite (HC) (n = 16). Eight samples were fatigued with 750,000 mechanical cycles and 8,000 thermal cycles between 5 and 55°C in a chewing simulator, and the failure mode was evaluated using a stereomicroscope and SEM. The other eight samples from each group were loaded to failure in a universal testing machine to test the fracture resistance. Fisher's exact Probability test was used to analyze the fatigue test results, and two-way analysis of variance and Bonferroni's test were used to analyze the fracture resistance test results.Results The difference in fatigue resistance between failure proportions in different groups was statistically different (p < 0.05). The 0.4-mm-thick UTLV had similar results regardless of the bonding technique, while 0.2-mm-thick UTLV only showed comparable results when cemented with preheated HC. No statistically significant difference was found in fracture resistance between the tested groups (p > 0.05).Conclusion The Bonding technique and the thickness of the UTLV had impacted fatigue resistance but had no significant effect on the fracture resistance. bonding of UTLV with preheated composite increases their fatigue resistance. Different testing approaches delivered different results.
Keywords: fatigue resistance; fracture resistance; laminate veneers; preheated composite; resin cement